Design of multi-magnetic couple MR damper with full channel effective damping. Issue 1 (June 2021) - Zhu, Yurui; Wang, Qun; Ma, Jichao; Tang, Zhanghong; Yu, Yunfei; Li, Yongqing
Abstract: A multi-magnetic couple magnetorheological damper with full channel effective damping is designed. By designing the magnetic outer ring of the magnetic couple into a structure with gradual cross-sectional area, the purpose of effective damping of the full channel can be achieved, so that the entire damping channel is affected by the magnetic field. Through the magnetic circuit simulation analysis, the rationality of the design is verified, and the magnetic induction intensity on the damping channel can reach the theoretical design value, which reflects the efficient magnetic field utilization rate of the damper.